Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1073/pnas.1111084108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation of historic phage-type 80/81 and contemporary epidemic Staphylococcus aureus

Abstract: Staphylococcus aureus is a bacterial pathogen known to cause infections in epidemic waves. One such epidemic was caused by a clone known as phage-type 80/81, a penicillin-resistant strain that rose to world prominence in the late 1950s. The molecular underpinnings of the phage-type 80/81 outbreak have remained unknown for decades, nor is it understood why related S. aureus clones became epidemic in hospitals in the early 1990s. To better understand the molecular basis of these epidemics, we sequenced the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
158
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 24 publications
12
158
1
Order By: Relevance
“…The current study extends the recent findings of DeLeo et al (12) who revealed the independent origin of phage 80/81 and SWP pandemics and identified mutations leading to reduced virulence among contemporary CC30 strains. The capacity to rapidly sequence the genome of large numbers of bacterial isolates can result in very enhanced insights into bacterial epidemics.…”
Section: Emrsa-16 Has Spread Within the United Kingdom By Transmissionsupporting
confidence: 75%
See 3 more Smart Citations
“…The current study extends the recent findings of DeLeo et al (12) who revealed the independent origin of phage 80/81 and SWP pandemics and identified mutations leading to reduced virulence among contemporary CC30 strains. The capacity to rapidly sequence the genome of large numbers of bacterial isolates can result in very enhanced insights into bacterial epidemics.…”
Section: Emrsa-16 Has Spread Within the United Kingdom By Transmissionsupporting
confidence: 75%
“…In their recent study, DeLeo and colleagues included a single EMRSA-16 isolate (MRSA252) and identified mutations in agr and hla genes, which occurred in an ancestor of MRSA252 and other contemporary CC30 isolates leading to reduced virulence in mouse models of infection (12). As proposed by the authors, these mutations may have contributed to the hospital association of contemporary CC30 isolates (4).…”
Section: Identification Of Mutations That Correlate With the Hospitalmentioning
confidence: 92%
See 2 more Smart Citations
“…In conclusion, the multiscale comparative approach used in this work provides insights into the diversity of the S. aureus species. Historical methods for classification of S. aureus strains have developed considerably from phage-typing to PFGE and MLST approaches (52). New high-throughput DNA sequencing technologies and analysis techniques will continue to improve our ability to track and distinguish pathogens.…”
Section: Discussionmentioning
confidence: 99%